HUBUNGAN ANTARA INTERAKSI SOSIAL DALAM KELUARGA DENGAN PERILAKU ASERTIF DI SMP NEGERI 7 PALEMBANG - Mawardah, Mutia (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2016)
This study aims to determine the relationship between social interaction in families with assertive behaviour among eighth grade students of junior high school 7 Palembang. The hypothesis proposed in this study is there a relationship between social interactionin families with assertive behaviour among eighth grade students of junior high school 7 Palembang. The population in this study were 360 subjects who are students of eight grade, and sampled as many as 177 subject. This research used simple random sampling technique, and Analysis techniques using simple regression analysis by using SPSS version 20.0 for windows. The results showed a correlation coefficient (r) of 0,654 with a coefficient of determination (R-square) of 0.746, and  p = 0,000 (p<0,01). This suggests that the hypothesis is accepted which showed that there is a significant relationship between social interaction in families with assertive behaviour among eighth grade students of junior high school 7 Palembang.